Defining Renal Recovery in Patients With Hepatorenal Syndrome‐Acute Kidney Injury: Experience From North American Studies - Muhammad A. Mujtaba; Hussien Elsiesy; Sara Faiz; Syed A. Hussain; Ann Kathleen N. Gamilla‐Crudo; Aftab Karim; Mohammad Irfan Khan; Muhammad Waqar Khattak; Zunaira Zafar; Michael Kueht; Khurram Jamil (JGH Open)
ABSTRACT Introduction The degree of improvement in serum creatinine (SCr) has previously been suggested as a sensitive indicator of treatment response in patients with hepatorenal syndrome‐acute kidney injury (HRS‐AKI), while HRS reversal remains the primary endpoint in clinical trials. Methods A total of ≥ 30% SCr improvement was analyzed as an exploratory prespecified endpoint in the CONFIRM trial. In this post hoc analysis, intent‐to‐treat population data from three Phase 3 studies (OT‐0401, REVERSE, and CONFIRM) conducted in North America in patients with HRS‐AKI were pooled to assess the incidence of > 30% improvement in SCr and its association with clinical outcomes. Results Significantly more patients treated with terlipressin achieved > 30% improvement in SCr compared with those who received a placebo (42.9% vs. 23.4%; p < 0.001). Compared with patients who did not achieve > 30% improvement in SCr, those who achieved this threshold had a lower incidence of renal replacement therapy (RRT) (55.2% vs. 14%, respectively; p < 0.001) and greater overall survival at Day 90 (41.6% vs. 71.1%, respectively; p < 0.001); a greater proportion achieved durability of HRS reversal (1% [95% confidence interval, 95% CI: 0] vs. 68.9% [95% CI: 0.6, 0.8]) and more patients were alive without RRT (22.7% vs. 61.6%, respectively; p < 0.001) or transplant (11.6% vs. 43.0%, respectively; p < 0.0001). Additionally, the overall survival and RRT‐free survival in the group that achieved > 30% improvement in SCr without HRS reversal were comparable to the overall group that achieved HRS reversal. Conclusion A total of > 30% improvement in SCr levels even without HRS reversal may serve as a clinically meaningful endpoint to define renal recovery in patients with HRS‐AKI.